Yttrium-doped hematite photoanodes for solar water splitting: Photoelectrochemical and electronic properties. Issue 11 (1st August 2018) - Käämbre, Tanel; Vanags, Martins; Pärna, Rainer; Kisand, Vambola; Ignatans, Reinis; Kleperis, Janis; Šutka, Andris
Abstract: We investigate yttrium-doped hematite thin-film photoelectrochemical properties and find yttrium incorporation to amply improve the performance as a photoanode for water splitting under visible light. We used the spray pyrolysis method to prepare a set of yttrium doped Fe2-x Yx O3 (x = 0, 0.05, 0.10, 0.15, 0.2) thin films (thickness below 500 nm) on glass and transparent conductive oxide coated glass slides. Using a substitutional homovalent (Y 3+ ) dopant, the effect on functionality is rationalised as a combined effect on the electronic structure and small polaron mobility from the lattice structure, impurity levels, lattice stability and variance in hybridisation. The photoelectrochemical response measurements indicate highest performance at Fe1.9 Y0.1 O3 composition.